Takotsubo syndrome triggered by emotional stress: a case report - Mülayim, Emine (The European Research Journal, 2022)
Takotsubo syndrome is an acute cardiac syndrome characterized by transient systolic dysfunction of the left ventricle without coronary artery disease. It’s etiology has not been fully explained, physical and intense emotional stress triggers this syndrome so it is also called "broken heart syndrome" or "stress cardiomyopathy". Takotsubu syndrome has been reported that approximately 2% of patients presenting with acute coronary syndrome. In this case, we presented a 65-year-old patient who had a Takotsubo syndrome attack after emotional stress, thinking that it would contribute to the literature and increase awareness of this disease.